2021
DOI: 10.1007/s00253-021-11336-5
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of the unfolded protein response pathway in Pichia pastoris: enhancing production of secreted recombinant proteins

Abstract: Folding and processing of proteins in the endoplasmic reticulum (ER) are major impediments in the production and secretion of proteins from Pichia pastoris (Komagataella sp.). Overexpression of recombinant genes can overwhelm the innate secretory machinery of the P. pastoris cell, and incorrectly folded proteins may accumulate inside the ER. To restore proper protein folding, the cell naturally triggers an unfolded protein response (UPR) pathway, which upregulates the expression of genes coding for chaperones … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 127 publications
0
36
0
Order By: Relevance
“…For instance, from the study of Zhong et al [38], it was observed that lowering the cultivation temperature from 30 to 20 • C aided in the upregulation of the UPR. The upregulation can increase the yield of the protein due to faster processing of the recombinant product within the ER [38,43]. A lower temperature is expected to reduce proteolysis and unfolding of the recombinant protein.…”
Section: Effect Of Induction Temperature On Recombinant Thaumatin II ...mentioning
confidence: 99%
“…For instance, from the study of Zhong et al [38], it was observed that lowering the cultivation temperature from 30 to 20 • C aided in the upregulation of the UPR. The upregulation can increase the yield of the protein due to faster processing of the recombinant product within the ER [38,43]. A lower temperature is expected to reduce proteolysis and unfolding of the recombinant protein.…”
Section: Effect Of Induction Temperature On Recombinant Thaumatin II ...mentioning
confidence: 99%
“…P. pastoris , an established protein expression host, is mainly applied for the production of biopharmaceuticals and industrial enzymes. This methylotrophic yeast is a distinguished production system for its growth to very high cell densities, the available strong and tightly regulated promoters, and the options to produce gram amounts of recombinant protein per liter of culture both intracellularly and in secretory fashion [ 29 ]. In this study, a β-glucosidase from B. circulans was expressed in P. pastoris .…”
Section: Resultsmentioning
confidence: 99%
“…Overexpression of Hac1p and Yap1p did not improve IgG secretion. Hac1p is a transcription factor regulating the UPR genes and its overexpression showed improvements in the production of secreted recombinant proteins [ 8 , 37 , 38 ]. YAP1 is another transcription factor involved in oxidative stress relief [ 39 ] for which an improved recombinant protein production by P. pastoris was reported [ 26 ].…”
Section: Discussionmentioning
confidence: 99%